The atherosclerosis-cancer axis: the shared immunotherapeutic potential of CBL inhibition - Jarr, Kai-Uwe; Luo, Lingfeng; Leeper, Nicholas J. (European heart journal, 2025)
This editorial refers to ‘The macrophage-derived motor protein KIF13B enhances MERTK-mediated efferocytosis and prevents atherosclerosis in mice’, by Y. Xu et al., https://doi.org/10.1093/eurheartj/ehaf523.Atherosclerosis, a chronic inflammatory disease, remains the leading cause of mortality in the industrialized world, followed closely by cancer.1 Despite its devasting impact, current antiatherosclerotic treatment strategies are largely centred solely around antiplatelet agents and aggressive lipid-lowering therapies. Unfortunately, even with these evidence-based interventions, cardiovascular mortality remains unacceptably high. This underscores a pressing need for fundamentally novel therapeutic strategies to combat this global health burden. A particularly promising avenue lies in harnessing innate immune surveillance, specifically through the cellular processes of phagocytosis and efferocytosis, suggesting that targeted immunotherapy may offer orthogonal, or potentially even synergistic,2 therapeutic solutions.3
Gesehen am 16.10.2025